Camptothecine production by mixed fermentation of two endophytic fungi from Nothapodytes nimmoniana. Issue 6 (June 2016) - Bhalkar, Bhumika N.; Patil, Swapnil M.; Govindwar, Sanjay P.
Abstract: Two endophytic fungi isolated from the endangered plant Nothapodytes nimmoniana (Grah.) Mabb. were found to effectively synthesize CPT independent of their host plant under submerged fermentation conditions. Molecular characterization of fungi revealed their identity as Colletotrichum fructicola SUK1 (F1) and Corynespora cassiicola SUK2 (F2). Mixed fermentation experiments were carried out to study the effect of microbial signalling between the two fungal species on camptothecine production. Effect of culture parameters on CPT production was studied for both mono-cultures (F1 and F2) separately as well as for the mixed fermentation (F1 + F2). Further the most influencing ones were optimized statistically using response surface methodology. Statistical model based optimized parameters were whey (70 %), agitation rate (110 rpm), temperature (30 °C), and incubation period (7 d) for the mixed fermentation. Monocultures of the two fungal species F1 and F2 yielded CPT up to 33 ± 1.1 mg l −1 and 69 ± 1.1 mg l −1, respectively; while their mixed fermentation under the optimized conditions yielded up to 146 ± 0.2 mg l −1 . HPLC and LC-MS/MS techniques were used to analyze the products obtained. Highlights: Isolation and identification of two endophytic fungi producing CPT. Enhanced production of CPT using mixed fermentation of two fungi. Optimization of process parameters for maximum CPT yield using RSM.